A history of liaison psychiatry in the UK. (August 2016) - Aitken, Peter; Lloyd, Geoffrey; Mayou, Richard; Bass, Christopher; Sharpe, Michael
Abstract : Aims and method: To record the development of liaison psychiatry in the UK and to summarise the current levels of activity. We also highlight the challenges the specialty may face if it is to develop further. History since the 1970s is reviewed by early pioneers and those involved in the present day, with a focus on the key role played by members of the Royal College of Psychiatrists. Results: We describe the development of training guidelines, the publication of joint documents with other Royal Colleges, establishing international collaborations and defining service specifications. We emphasise the importance of collaboration with other medical organisations, and describe successes and pitfalls. Clinical implications: Much has been achieved but challenges remain. Liaison psychiatry has a potentially important role in improving patient care. It needs to adapt to the requirements of the current National Health Service, marshal evidence for cost-effectiveness and persuade healthcare commissioners to fund services that are appropriate for the psychological needs of general hospital patients.